Enhancing The Methane Production From Biogas Effluent Of Palm Oil Mill Using Microbial Electrolysis Cell - Phatnarin Buakhao; Nu-Aime Baniahmad; Rattana Jariyaboon; Prawit Kongjan (Kolej Genius Insan, USIM, 2024)
E-Proceedings 3rd Insan Junior Researchers International Conference 2022 (iJURECON 2022) : "STREAM for a better future”/Editors: Rahayu Ahmad, Muhammad Azan Tamar Jaya, Ahmad Fuad Mohamad Amin, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan. 21-23rd October 2022 (Virtual Conference) Organized By : Kolej Genius Insan,USIM